DETERMINATION OF POLYSORBATES BY SPECTROPHOTOMETRY IN DRUGS BASED ON RECOMBINANT PROTEINS - A. D. Askretkov; P. M. Isaykina; S. A. Cherepushkin; N. V. Orlova (Разработка и регистрация лекарственных средств, 2019)
Method of determination of polysorbate 20 and polysorbate 80 in recombinant protein drugs based on spectrophotometry has been designed. Isolation of polysorbate from solution is carried out by solid phase extraction followed by elution of polysorbate with acetonitrile. Acetonitrile solution is evaporated and then polysorbate is derivatized with ferrous-thiocyanate reagent. Obtained derivative is extracted into organic phase and optical density is measured. The most optimal conditions of derivatization, extraction into organic phase and measurment was chosen. The validation was performed: specificity, linearity, accuracy, precision, robustness, limit of quantification.